The determinant factors for ethical judgments / Maheran Zakaria, Junaidah Hanim Ahmad and Nazmi Mohamed Zin - Zakaria, Maheran; Ahmad, Junaidah Hanim; Mohamed Zin, Nazmi (2011)
The public has been dismayed and angered by the catastrophic collapse of giant corporations throughout the world such as Enron, Xerox, WorldCom, Parmalat, Tyco and Barings Bank, which resulted from a succession of financial scandals. Such unfortunate scandals have also happened in Malaysia, such as those involving Transmile Group, Perwaja and Southern Bank. The fact that these scandals are becoming more frequent these days has spurred interest in studies of ethics. In addition, the public always associate these unethical scandals with unethical judgments. In light of this issue, the objective of this study is to examine the determinant factors for ethical judgments. Three hypothesized relationships were tested using the samples of 260 Universiti Teknologi MARA Kelantan Accounting students. The results derived from the regression analyses concluded that knowledge of ethics and religiosity are strongly associated with ethical judgments. However, organizational ethical climate does not have any relationship with ethical judgments. The empirical results provide an insight for higher learning institutions in cultivating future accountants' ethical judgments towards nurturing a fully ethical society.